Data presented in the paper "Invasive oysters as new hosts for native shell-boring polychaetes: using historical shell collections and recent field data to investigate parasite spillback in native mussels in the Dutch Wadden Sea" - Waser, A.M. Andreas; Knol, J. Jeffrey; Dekker, R. Rob; Thieltges, D.W. David (4TU.ResearchData, 2021)
Research objective: We investigated the potential spillback of the native shell-boring polychaete Polydora ciliata from invasive Pacific oysters (Crassostrea (Magallana) gigas) to native mussels (Mytilus edulis) in the Dutch Wadden Sea by means of a field survey and historical collections of M. edulis shells. Type of research, method & collection of data: We sampled dead and alive specimens of blue mussels, Pacific oysters and periwinkles (Littorina littorea) at three intertidal locations at the Wadden Sea island Texel in order to determine host preferences of P. ciliata. To test, whether P. ciliata infections in mussels changed after the invasion of the Pacific oyster, we analysed x-ray images for P. ciliata burrows in mussel shells stemming from long-term monitoring campaigns from intertidal and subtidal areas of the western Dutch Wadden Sea.